Southern Ocean biogenic blooms freezing-in Oligocene colder climates - Hochmuth, Katharina; Whittaker, Joanne M.; Sauermilch, Isabel; Klocker, Andreas; Gohl, Karsten; LaCasce, Joseph H. (Nature Communications, 2022)
Crossing a key atmospheric CO2 threshold triggered a fundamental global climate reorganisation ~34 million years ago (Ma) establishing permanent Antarctic ice sheets. Curiously, a more dramatic CO2 decline (~800–400 ppm by the Early Oligocene(~27 Ma)), postdates initial ice sheet expansion but the mechanisms driving this later, rapid drop in atmospheric carbon during the early Oligocene remains elusive and controversial. Here we use marine seismic reflection and borehole data to reveal an unprecedented accumulation of early Oligocene strata (up to 2.2 km thick over 1500 × 500 km) with a major biogenic component in the Australian Southern Ocean. High-resolution ocean simulations demonstrate that a tectonically-driven, one-off reorganisation of ocean currents, caused a unique period where current instability coincided with high nutrient input from the Antarctic continent. This unrepeated and short-lived environment favoured extreme bioproductivity and enhanced sediment burial. The size and rapid accumulation of this sediment package potentially holds ~1.067 × 1015 kg of the ‘missing carbon’ sequestered during the decline from an Eocene high CO2-world to a mid-Oligocene medium CO2-world, highlighting the exceptional role of the Southern Ocean in modulating long-term climate.
Keywords: Sørishavet; geologi; glasiologi; klimaendringer; sedimenter

Variability of Sediment Accumulation Rates in an Antarctic Fjord - Eidam, Emily F.; Nittrouer, Charles; Lundesgaard, Øyvind; Homolka, Khadijah; Smith, Craig (Geophysical Research Letters, 2019)
Fjords on the West Antarctic Peninsula (WAP) serve as sediment traps, preserving histories of glacial sediment supply. Regional warming trends are expected to change sediment supplies, altering water quality, depositional history, and ecosystem drivers. Our ability to assess magnitudes of these changes is limited by sparse data on modern sediment accumulation. Twelve new cores and four existing cores from Andvord Bay were used to characterize variability in sediment accumulation rates. These range from 1.5 to 7.9 mm/year (0.12 to 0.56 g·cm−2·year−1). Spatial differences and a weak down-fjord gradient in rates suggest diverse sediment sources, including from outside the fjord. This data set provides a comprehensive assessment of sedimentation during the past century, indicating little change in rates due to recent WAP warming, and sets a benchmark for assessing climate-related changes in sediment delivery and ecosystem drivers (e.g., burial disturbance) in the fjord over coming decades.
Keywords: Antarktis; akkumulasjon; bentiske organismer; biodiversitet; fjord; glasiologi; sedimenter; sedimentologi; tidevannsbreen

GlobSed: Updated Total Sediment Thickness in the World's Oceans - Straume, Eivind O; Gaina, Carmen; Medvedev, Sergei; Hochmuth, Katharina; Gohl, Karsten; Whittaker, Joanne; Abdul Fattah, R; Doornenbal, J C; Hopper, John R (Geochemistry, Geophysics, Geosystems, 2019)
We present GlobSed, a new global 5-arc-minute total sediment thickness grid for the world's oceans and marginal seas. GlobSed covers a larger area than previously published global grids and incorporates updates for the NE Atlantic, Arctic, Southern Ocean, and Mediterranean regions, which results in a 29.7% increase in estimated total oceanic sediment volume. We use this new global grid and a revised global oceanic lithospheric age grid to assess the relationship between the total sediment thickness and age of the underlying oceanic lithosphere and its latitude. An analytical approximation model is used to mathematically describe sedimentation trends in major oceanic basins and to allow paleobathymetric reconstructions at any given geological time. This study provides a much-needed update of the sediment thickness distribution of the world oceans and delivers a model for sedimentation rates on oceanic crust through time that agrees well with selected drill data used for comparison.
Keywords: Sørishavet; batymetri; litosfæren; marin geofysikk; marin geologi; sedimenter; sedimentologi

Climate controlled sedimentary processes in the Riiser Larsen Sea offshore Queen Maud Land, Antarctica: master's thesis in geology - Brekken, Rita (UiT: University of Tromsø, 2018)
Keywords: Sørishavet; geologi; sedimenter

Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto (Polar Research, 2016)
It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity. Keywords: Biodiversity; photosynthetic pigments; proxy; continental Antarctica; sediments; biogeography.
Keywords: Antarktis; alger; biodiversitet; biogeografi; biomasse; ferskvann; fotosyntese; innsjø; sedimenter; økologi

Local controls on sediment accumulation and distribution in a fjord in the West Antarctic Peninsula: implications for palaeoenvironmental interpretations - Munoz, Yuribia P.; Wellner, Julia S. (Polar Research, 2016)
We analyse surface sediment and its distribution in Flandres Bay, West Antarctic Peninsula, in order to understand modern day sediment dispersal patterns in a fjord with retreating, tidewater glaciers. The surface sediment descriptions of 41 cores are included in this study. The sediment facies described include muddy diatomaceous ooze, diatomaceous mud, pebbly mud, sandy mud and mud, with scattered pebbles present in most samples. In contrast to a traditional conceptual model of glacial sediment distribution in fjords, grain size in Flandres Bay generally coarsens from the inner to outer bay. The smallest grain size sediments were found in the bay head and are interpreted as fine-grained deposits resulting from meltwater plumes and sediment gravity flows occurring close to the glacier front. The middle of the bay is characterized by a high silt percentage, which correlates to diatom-rich sediments. Sediments in the outer bay have a high component of coarse material, which is interpreted as being the result of winnowing from currents moving from the Bellingshausen Sea into the Gerlache Strait. Palaeoenvironmental reconstructions of glacial environments often use grain size as an indicator of proximity to the ice margin. After a detailed analysis of a large number of cores collected in the study area, our findings highlight the variability in sedimentation patterns within a fjord and provide a valuable evidence of the complexity that may occur in the sedimentary record. Keywords: Flandres Bay; Antarctic Peninsula; sediment distribution; grain size.
Keywords: Antarktis; havbunnen; isbreer; miljøvitenskap; sedimenter; sedimentologi; topografi

Using visible reflectance spectroscopy to reconstruct historical changes in chlorophyll a concentration in East Antarctic ponds - Chen, Qianqian; Liu, Xiaodong; Nie, Yaguang; Sun, Liguang (Polar Research, 2013)
The visible reflectance spectroscopy (VRS) and chlorophyll a concentration were determined in three sediment profiles collected from East Antarctica to investigate the potential application of VRS in reconstructing historical changes in Antarctic lake primary productivity. The results showed that the appearance of a trough at 650–700 nm is an important marker for chlorophyll a concentration and can therefore be used to distinguish the sedimentary organic matter source from guano and algae. The measured chlorophyll a content had significant positive correlations with the trough area between 650 and 700 nm, and no distinct trough was found in the sediments with organic matter completely derived from guano. Modelling results showed that the spectra spectrally inferred chlorophyll a content, and the measured data exhibit consistent trends with depth, showing that the dimensionless trough area can serve as an independent proxy for reconstructing historical fluctuations in the primary production of Antarctic ponds. The correlation of phosphorus (P) with measured and inferred chlorophyll a contents in ornithogenic sediments near penguin colonies indicates that the change in primary productivity in the Antarctic ponds investigated was closely related to the amount of guano input from these birds. Keywords: Reflectance spectroscopy; ornithogenic sediments; chlorophyll a; Antarctic ponds; primary productivity; VRS.
Keywords: Antarktis; alger; biogeokjemi; fytoplankton; innsjø; pingviner; sedimenter; sjøfugler

Sources and geographic heterogeneity of trace metals in the sediments of Prydz Bay, East Antarctica - Sun, Wei-Ping; Hu, Chuan-Yu; Weng, Huan-Xin; Han, Zheng-Bing; Shen, Chen; Pan, Jian-Ming (Polar Research, 2013)
In this study, we have determined the contents and distribution of zinc and cadmium in the surface sediments from Prydz Bay, East Antarctica. The main sources of the trace elements and their geographic heterogeneity, and the relation between Zn and Cd, are discussed based on the cluster analysis, principle component analysis and considerations of biogenic and lithogenic inputs. The results show that the contents of trace metals range from 34.6 to 96.6 mg kg-1 for Zn, and from 0.254 to 0.441 mg kg-1 for Cd. Calculations of the enrichment factor indicated no significant anthropogenic impact. Biogenic and lithogenic inputs are the main sources of trace metals. They are almost equal for Zn and Cd at the Amery Ice Shelf edge, while the continental shelf and deep ocean are dominated by biogenic inputs. The contribution of biogenic inputs is much higher for Zn than for Cd at the deep ocean. Calculations of biogenic trace metals revealed different relationships between biogenic Zn and biogenic Cd, which reflect the biological uptake by phytoplankton in the water column. Keywords: Trace elements; sources; enrichment factor; cluster analysis; principal component analysis; Antarctica.
Keywords: Sørishavet; fytoplankton; geografi; kjemiske analyser; kontinentalmargin; kontinentalsokkel; marin biologi; oseanografi; sedimenter; sedimentologi

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

The Cosmonaut Sea Wedge - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandyukhin, V (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; sedimenter

Postglacial marine environmental changes in Maxwell Bay, King George Island, West Antarctica - Khim, Boo-Keun; Yoon, Ho Il (Polar Research, 2003)
Sediment textural properties and total organic carbon (TOC) contents of three sediment cores from Maxwell Bay, King George Island, West Antarctica, record changes in Holocene glaciomarine sedimentary environments. The lower sedimentary unit is mostly composed of TOC-poor diamictons, indicating advanced coastal glacier margins and rapid iceberg discharge in proximal glaciomarine settings with limited productivity and meltwater supply. Fine-grained, TOC-rich sediments in the upper lithologic unit suggest more open water and warm conditions, leading to enhanced biological productivity due to increased nutrient-rich meltwater supply into the bay. The relationship between TOC and total sulfur (TS) indicates that the additional sulfur within the sediment has not originated from in situ pyrite formation under the reducing condition, but rather may be attributed to the detrital supply of sand-sized pyrite from the hydrothermal-origin, quartz-pyrite rocks widely distributed in King George Island. The evolution of bottom-water hydrography after deglaciation was recorded in the benthic foraminiferal stable-isotopic composition, corroborated by the TOC and lithologic changes. The Ø18O values indicate that bottom-water in Maxwell Bay was probably mixed gradually with intruding 18O-rich seawater from Bransfield Strait. In addition, the Ø13C values reflect a spatial variability in the carbon isotope distribution in Maxwell Bay, depending on marine productivity as well as terrestrial carbon fluxes by meltwater discharge. The distinct lithologic transition, dated to approximately 8000 yr BP (uncorrected) and characterized by textural and geochemical contrasts, highlights the postglacial environmental change by a major coastal glacier retreat in Maxwell Bay.
Keywords: Sørishavet; geofysikk; geokjemi; marin geologi; miljøendringer; sedimenter

Klimavariasjoner gjennom de siste 45 000 14C år i Weddellhavet, Antarktis - Larsen, Anne Marit Løland (Universitetet i Bergen, 2001)
Keywords: Sørishavet; Weddellhavet; maringeologi; paleoklimatologi; sedimenter

Quantitative models for reconstructing catchment ice-extent using physical-chemical characteristics of lake sediments - Noon, P.E.; Birks, H.J.B.; Jones, V.J.; Ellis-Evans, J.C. (Journal of Paleolimnology, 2001)
The physical characteristics of surface sediments from a suite of pristine lakes on Signy Island, maritime Antarctic, were used to develop a quantitative link between catchment ice-extent and lake-sediment response. Percentage dry weight, median particle size, percentage loss-on-ignition and wet density of the lakes' surface sediments were the most significant variables explaining contemporary catchment ice-extent. Two independent reconstruction models – Partial Least Squares (PLS) and a Modern Analog Technique (MAT) – were applied to dated sediment cores at two sites on Signy Island. The validity of the reconstructions was tested against historical information on catchment ice-extent. With sufficiently high sedimentation rates and sampling resolution, the models can predict sub-decadal changes in ice-extent. The model results are best regarded as indicators of erosion resulting from meltwater activity in the catchment. Comparison of results with Twentieth Century climate records affirms the hypothesis that climatic warming is the most likely cause for the ice retreat observed on Signy Island during the last 40 yrs. Similar reconstruction models using these simple sedimentary measures could be developed for analogous locations in the Antarctic and in Arctic and Alpine regions.
Keywords: Antarktis; innsjø; klimaendringer; paleolimnologi; sedimenter; økologi

Chemical composition in water masses and interactions with the sediment in the southern Weddel sea - Anderson, Leif G; Fogelqvist, Elisabet; Hulth, Stefan; Olsson, Kristina; Tanhua, Toste; Tengberg, Anders; Zemlyak, Frank (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; analyser; kjemisk; sedimenter; vannmasser

Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Characteristics of Weddell Sea Shelf sediments obtained by diamond core drilling, Antarctica - Strand, Kari; Kristoffersen, Yngve (FINNARP -95/96: Weddel Sea Joint Nordic Expedition, 1997)
Keywords: Sørishavet; geokjemi; sedimenter

Glaciomarine sediments and suspended particulate matter, Weddell sea, Antarctica (abstract only) - Elverhøi, Anders; Roaldset, Elen (Annals of Glaciology, 1981)
Samples of glaciomarine sediments and suspended particulate matter filtered from sea-water were collected in the Weddell Sea during the Norwegian Antarctic Research Expedition (NARE) in 1978–79. Analyses have provided information on the textural and mineralogical composition of shelf sediments, on the nature of biogenic and inorganic suspended particulate matter, and on the total sediment transport to the shelf areas and further into the deeper waters (). The shelf waters contain 0.1 to 1.2 g m–3 of suspended particulate matter, which is close to the range of 0.5 to 1.5 g m–3 reported for suspension concentrations in the oceans, but considerably lower than that found for some other glaciomarine environments such as the Bering Sea {up to 13-15 g m–3 ()) and off Kongsbreen, Spitsbergen {up to 500 g m–3 ()). Suspended particles from the Weddell Sea have maximum sizes of 50 to 70 µm and mean diameters in the range of 10 to 20 µm. In contrast, the bottom sediments on the outer shelf are deficient in the corresponding fractions. This reflects that when floating Antarctic ice supplies material to the Weddell Sea, the coarser fragments (>20-70 µm) are deposited, while the medium silt and finer fractions go into suspension. Considering the suspended-load data and the bottom-current measurements on the shelf break, it is evident that in January 1979 an average of 8.6 × 104tonnes d–1 (or 32 × 106 tonnes a–l) of particulate matter was transported by the current from the central Weddell Sea to the South Atlantic deep water. Morphological (scanning electron microscopy) and chemical analyses show the suspended material to be dominated by silica organisms (diatoms), and also to contain clastic grains of phyllosilicates, feldspar, quartz, zircon, in a few cases Al- and Fe-hydroxides/oxides also; authigenic “Fe-sepiolite” and secondary gypsum. Mineralogical analyses (X-ray diffraction) of the bottom sediments show the fine sand silt fractions to contain mainly clastic materials like illite, smectite-vermiculite, and quartz. Biogenic silica (cristobalite) and carbonate (Mg-calcite) as well as authigenic Fe-silicates (“Fe-sepiolite”) are also present.
Keywords: Sørishavet; glasiologi; sedimenter